Volume 2: Emissions Control Systems; Instrumentation, Controls, and Hybrids; Numerical Simulation; Engine Design and Mechanical 2017
DOI: 10.1115/icef2017-3603
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Multi-Cycle LES of an Optical Pent-Roof DISI Engine Under Motored Operating Conditions

Abstract: The use of Large-eddy Simulations (LES) has increased due to their ability to resolve the turbulent fluctuations of engine flows and capture the resulting cycle-to-cycle variability. One drawback of LES, however, is the requirement to run multiple engine cycles to obtain the necessary cycle statistics for full validation. The standard method to obtain the cycles by running a single simulation through many engine cycles sequentially can take a long time to complete. Recently, a new strategy has been proposed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The individual simulations are then run for two cycles, using only the second cycle for data analysis. This same methodology was also used for the previous study by the authors on pure motored flow and found the correlation between the parallel and sequential cycles to be very high while significantly reducing the wall-clock time to complete the same number of engine cycles [48]. For the current study, each engine cycle took approximately 40 hours on 48 processors, or about 100 hours per usable cycle including the initial PPM cycles.…”
Section: Iso-pentane 27%mentioning
confidence: 61%
See 2 more Smart Citations
“…The individual simulations are then run for two cycles, using only the second cycle for data analysis. This same methodology was also used for the previous study by the authors on pure motored flow and found the correlation between the parallel and sequential cycles to be very high while significantly reducing the wall-clock time to complete the same number of engine cycles [48]. For the current study, each engine cycle took approximately 40 hours on 48 processors, or about 100 hours per usable cycle including the initial PPM cycles.…”
Section: Iso-pentane 27%mentioning
confidence: 61%
“…This happens despite the fact that the simulations also over-predict the trapped mass (304 mg in simulations vs. an estimated 280 mg for experiments). Previously published comparisons of motored engine simulations without fuel spray showed an under-prediction of the cylinder pressure of 1.5% with similar differences in trapped mass [48]. A possible explanation for the greater difference in peak pressure with the fuel injection is the uncertainty associated with the fuel's heat of vaporization (HoV).…”
Section: Global Datamentioning
confidence: 98%
See 1 more Smart Citation
“…A more general approach is to consider the entire flow field by calculating differences in RMS velocities over the whole field (Van Dam et al 2018). Statistical methods such as the circular standard deviation can also be used to investigate cyclic variability in velocity magnitudes and directions (Van Dam and Rutland 2015) and flow field differences between sequential and parallel LES simulations (Van Dam et al 2017).…”
Section: Methods For Comparing Vector Fieldsmentioning
confidence: 99%
“…The MSI produces values between 0 and 1 with larger values corresponding to better alignment. This metric has been used to investigate the convergence of simulated OH mass fraction and soot mass fraction distributions of an n-dodecane spray flame (Ameen et al 2016) and to quantify flow field differences between simulations and experiments (Ameen et al 2017;Van Dam et al 2017). Similarly to the MSI, the local magnitude index (LMI), defined using magnitude subtraction rather than vector subtraction, has recently been used to compare LES simulations to PIV measurements across five planes within an optical engine (Zhao et al 2019).…”
Section: ) Defined Asmentioning
confidence: 99%